Getting lost with dementia: Encounters with the time-space of not knowing. (November 2022) - Ward, Richard; Rummery, Kirstein; Odzakovic, Elzana; Manji, Kainde; Kullberg, Agneta; Clark, Andrew; Campbell, Sarah
Abstract: In this paper we explore the experience and implications of getting lost with dementia. While getting lost has become culturally emblematic of dementia, speaking as it does to a widespread fear of losing our place in the world, it is marked by an overall absence of critical attention. We argue that this critical hesitancy is part of a broader unease with 'dementing' that reveals a paradox in dementia scholarship as growing emphasis on strengths-based and capacity-oriented approaches to the condition shift attention away from episodes of disorientation, forgetting and unknowing that commonly arise after onset. We therefore explore getting lost with dementia, not only as a route to better understanding what happens during such events and the meaning it holds but also to consider the implications for a broader politics of the social inclusion of people living with dementia. Reporting findings from a five-year international study of the neighbourhood experiences of people with dementia, we suggest that through such experiences as getting lost, people with dementia have a unique and distinctive contribution to make to the ever-evolving character of public space and civic culture. In particular, we argue that getting lost and the subsequent recovery or reconstitution that ensues can help inform efforts to reimagine public space. This includes looking beyond risk reduction in responses to dementia and public and outdoor settings to consider how freedom of movement for people with dementia might be enhanced rather than curtailed. Our learning points to the value of making the process of dementing more visible and central to the politics and practices of social inclusion. Highlights: Offers critical examination of under-researched aspects of the experience of dementia. Highlights how experiences of dementia can inform understanding of public space. Demonstrates the policy relevance of a situated account of dementia. Illuminates understanding of the relationship between dementia and place.